A Collaborative Study to Establish the 6th International Standard for Factor VIII Concentrate - Raut, S.; Heath, A. B.; Barrowcliffe, T. W. (Thrombosis and Haemostasis, 2001)
A study was carried out to replace the 5th WHO International Standard (IS) for factor VIII concentrate, because of depletion of stocks. Two candidate concentrates (X and Y) were assayed as potential replacements against the 5th IS for FVIII concentrate, in a collaborative study involving 33 laboratories. Collaborators were asked to use the ISTH/SSC recommendations, including pre-dilution of concentrates in FVIII deficient plasma in their assays. Several laboratories performed more than one assay method and altogether there were 21 sets of assays with the one-stage method, 6 with the two-stage method and 26 with the chromogenic method. There was good agreement between laboratories using each method for the comparison of concentrates X and Y against the 5th IS, but the overall potencies by one-stage and chromogenic methods each differed by approximately 5% from the overall mean, with the chromogenic potency approximately 10% higher than the one-stage. Inter-laboratory agreement was slightly better for concentrate Y than X, and stability studies indicated that Y was more stable than X. After considering all the information, together with comments from participants and from the FVIII/FIX Subcommittee of the ISTH/SSC, candidate Y (NIBSC code [97/616]), was proposed and accepted in October, 1998, by the Expert Committee on Biological Standardisation of the World Health Organisation to be the 6th International Standard for Factor VIII Concentrate with an assigned potency of 8.5 IU/ampoule.
Keywords: Factor VIII concentrate; international standard